2007
DOI: 10.1128/aac.00107-07
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characteristics, and Molecular Epidemiology of Macrolide and Fluoroquinolone Resistance in Clinical Isolates of Streptococcus pneumoniae at Five Tertiary-Care Hospitals in Korea

Abstract: The genes erm(B), mef(A), and both erm(B) and mef(A) were identified in 42.6, 10.1, and 47.3%, respectively, of the erythromycin-resistant Streptococcus pneumoniae isolates. Of the strains, 3.8% were nonsusceptible to levofloxacin and had 1 to 6 amino acid changes in the quinolone resistance-determining region, including a new mutation, Asn94Ser, in the product of parC. Levofloxacin with reserpine was highly specific for efflux screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
(14 reference statements)
1
6
0
1
Order By: Relevance
“…Among the MRSP tested, 94.8% (92/97) were erm-or erm + mef-positive. This result is consistent with previous studies of strains isolated from Shanghai and other Asian cities [11,17,[31][32][33] showing a predominance of macrolide resistance associated with the erm(B) gene. Macrolide resistance in strains from North America are primarily associated with efflux pumps via the mef(E) gene, although an increase in strains harbouring both the erm and mef genes is evident from recent studies [3,34,35].…”
Section: Discussionsupporting
confidence: 94%
“…Among the MRSP tested, 94.8% (92/97) were erm-or erm + mef-positive. This result is consistent with previous studies of strains isolated from Shanghai and other Asian cities [11,17,[31][32][33] showing a predominance of macrolide resistance associated with the erm(B) gene. Macrolide resistance in strains from North America are primarily associated with efflux pumps via the mef(E) gene, although an increase in strains harbouring both the erm and mef genes is evident from recent studies [3,34,35].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that erythromycin resistance and MDR of all pneumococci from 20 primary clinics were 82.9% and 56.1%, respectively, which are similar to previous data based on some tertiary hospitals in Korea. 25,26 However, as we applied the new CLSI breakpoint of S. pneumoniae for penicillin in this study, the rate of nonsusceptibility was 27.9% (but the penicillin resistance was 80.4% based on the previous breakpoint for penicillin of CLSI). Of note, the full resistance rate was only 4.0% (MIC !8 mg=ml).…”
Section: Discussionmentioning
confidence: 96%
“…Marked differences among pneumococcal isolates have been reported worldwide, and especially high non‐susceptibility rates of up to 81.6% are found in Asia [6,21]. Although increasing rates of fluoroquinolone resistance have been described in some previous reports, especially for Hong Kong and Korea, but also for Canada, the USA, Mexico, and Japan, the rate of resistance remains relatively low worldwide [21,23–27]. While levofloxacin resistance was very low or absent in other European countries, in Germany the level of levofloxacin non‐susceptibility detected (0.4%) has remained at the same level as recorded in 2001–2003 [26].…”
Section: Discussionmentioning
confidence: 99%